Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1042/bst0120184
|View full text |Cite
|
Sign up to set email alerts
|

The ADP-ribosyltransferase activity of cholera toxin and Escherichia coli heat-labile toxin

Abstract: Cholera toxin CT, an enterotoxin produced by Vibrio cholerae, is responsible for the clinical manifestation of cholera which is characterized by severe fluid loss from the small intestine. The toxin acts by irreversibly stimulating adenylate cyclase in the basolateral membrane of the intestinal cell to raise cyclic AMP levels (Kimberg et al., 1971 ; Sharp & Hynie, 1971). CT is a 84000-M, protein composed of two types of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…An epidemiologic study (238) demonstrated that E. coli 0148K/H28 was responsible for the disease known as "travellers' diarrhoea" or the "Aden trot" among British soldiers in Aden. These pathogenic E. coli serotypes were found to elaborate an enterotoxin with activity very similar to that of CT (37,105). The two toxins are closely related immunologically, and cholera antitoxin neutralizes the ability of LT to cause fluid accumulation in the ileal loop test (119).…”
Section: History and Genetics Of E Coli-associated Diarrheamentioning
confidence: 99%
“…An epidemiologic study (238) demonstrated that E. coli 0148K/H28 was responsible for the disease known as "travellers' diarrhoea" or the "Aden trot" among British soldiers in Aden. These pathogenic E. coli serotypes were found to elaborate an enterotoxin with activity very similar to that of CT (37,105). The two toxins are closely related immunologically, and cholera antitoxin neutralizes the ability of LT to cause fluid accumulation in the ileal loop test (119).…”
Section: History and Genetics Of E Coli-associated Diarrheamentioning
confidence: 99%
“…The binding of GTP to the regulatory protein activates adenylate cyclase and the hydrolysis of the GTP turns off the stimulated adenylate cyclase. By blocking the hydrolysis of GTP, CT caused the permanent activation of adenylate cyclase, thus, cAMP levels are raised (Fishman, 1980;Coulson et al, 1984). After CT is applied to the mucosa of the small intestine, a lag period of approximately 30 minutes occurs before an effect on fluid transport can be detected.…”
Section: Localization Of Absorptive and Secretory Processesmentioning
confidence: 99%